2017
DOI: 10.1007/s10047-017-0957-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of endothelialization in the center part of graft using 3 cm vascular grafts implanted in the abdominal aortae of the rat

Abstract: In order to develop small-diameter vascular grafts, it is necessary to evaluate endothelialization, especially, in the center part at early stage. For implantation of vascular grafts of 1 cm in length to abdominal aortae of rat, endothelial cells can be formed easily by stretching anastomosis. We evaluated the endothelialization in the center part of vascular grafts by implanting vascular grafts using transgenic (TG) silk fibroin (SF) of 3 cm in length. Vascular grafts were prepared 1.5 mm in diameter and 1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…This result was also better than reported in previous studies using transgenic silk. 22 Endothelialization at the center of the artificial blood vessel is formed by extension from the anastomotic portion and capillary invasion from the outside to the inside of the graft. 51 Because invasion of the self-tissue including capillary vessels are quite important for endothelialization in this way, it is thought that the coating which is degraded early and accelerates remodeling functions advantageously for endothelialization.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This result was also better than reported in previous studies using transgenic silk. 22 Endothelialization at the center of the artificial blood vessel is formed by extension from the anastomotic portion and capillary invasion from the outside to the inside of the graft. 51 Because invasion of the self-tissue including capillary vessels are quite important for endothelialization in this way, it is thought that the coating which is degraded early and accelerates remodeling functions advantageously for endothelialization.…”
Section: Discussionmentioning
confidence: 99%
“…10 Recently, it has been used as an excellent biomaterial because of the ability to fabricate silk into a wide range of materials with tunable mechanical and degradation properties. 11,12 In the last decade, our group [13][14][15][16][17][18][19][20][21][22] and other groups [23][24][25][26] have shown that SF is an excellent candidate for vascular grafts on the basis of in vivo implant data with rats and/or dogs. SF vascular grafts prepared in our studies [15][16][17][18][19][20][21][22] consist of the SF fiber base coated with the SF sponge.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the experiment would have to be repeated for results to be confirmed. The use of transgenic silk was reported again in 2017: Fukayama et al 86 created braided scaffolds using silk fibroin incorporating a vascular endothelial growth factor (VEGF) gene. The interest in VEGF is due to its properties mediating ECs growth and migration.…”
Section: Vascular-shaped Scaffoldsmentioning
confidence: 99%